Physiological and Immune-Biological Characterization of a Long-Term Murine Model of Blunt Chest Trauma. Issue 2 (February 2015) - Hafner, Sebastian; Wagner, Katja; Wepler, Martin; Matallo, José; Gröger, Michael; McCook, Oscar; Scheuerle, Angelika; Huber-Lang, Markus; Frick, Manfred; Weber, Sandra; Stahl, Bettina; Jung, Birgit; et al.
<x xml:space="preserve">Abstract</x> ABSTRACT Blunt chest trauma causes pulmonary and systemic inflammation. It is still a matter of debate whether the long-term course of this inflammatory response is associated with persistent impairment of lung function. We hypothesized that an increase of inflammatory biomarkers may still be present at later time points after blunt chest trauma, eventually, despite normalized lung mechanics and gas exchange. Anesthetized spontaneously breathing male C57BL/6J mice underwent a blast wave–induced blunt chest trauma or sham procedure. Twelve and 24 h later, blood gases and lung mechanics were measured, together with blood, bronchoalveolar lavage (BAL), and tissue cytokine concentrations (multiplex cytokine kit); heme oxygenase 1 (HO-1), activated caspase-3, Bcl-xL, and Bax expression (Western blotting); nuclear factor-κB activation (electrophoretic mobility shift assay); nitrotyrosine formation; and purinergic (P2XR4 and P2XR7) receptor expression (immunohistochemistry). Histological damage was assessed by hematoxylin and eosin and periodic acid-Schiff staining. High-resolution respirometry allowed assessing mitochondrial respiration in diaphragm biopsies. Chest trauma significantly increased tissue and BAL cytokine levels, associated with a significant increase in HO-1, purinergic receptor expression, and tissue nitrotyrosine formation. In contrast, lung mechanics, gas exchange, and histological damage did not show any significant difference between sham and trauma groups. Activation of the immune response remains present at later time points after murine blunt chest trauma. Discordance of the increased local inflammatory response and preserved pulmonary function may be explained by a dissociation of the immune response and lung function, such as previously suggested after experimental sepsis.